The Influence of Herding Behavior and Overconfidence Bias on Investment Decisions of Millennial Generation Cryptocurrency Investors in Malang City - Kalimasada; Yasin Nur Rohim (PT FORMOSA CENDEKIA GLOBAL, 2023)
This exploration aims to dissect the influence of herding behavior and overconfidence-bias on investment decisions by millennial generation Cryptocurrency investors in Malang City. This type of research is explanatory research with a quantitative approach. This research aims to test and explain the influence of the direct relationship between the variables herding behavior and overconfidence-bias on investment decisions by cryptocurrency investors through hypothesis testing. This research has a sample size of 99 Millennial Generation Cryptocurrency investors in Malang City which was obtained through distributing a Google Form questionnaire using a purposive sampling technique. This research uses the F-test with the SPSS 23 application. The results of this research show that the herding behavior variable has a significant effect on investment decisions. However, this is different, the overconfidence_bias variable does not have a significant effect on investment decisions by millennial generation Cryptocurrency investors in the city of Malang.